2009
DOI: 10.1074/jbc.m808949200
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-8 Induces Apoptosis in Jurkat T Cells by Phosphatidic Acid-mediated ERK1/2 Activation Supported by Protein Kinase A Down-regulation

Abstract: Galectins have been implicated in T cell homeostasis playing complementary pro-apoptotic roles. Here we show that galectin-8 (Gal-8) is a potent pro-apoptotic agent in Jurkat T cells inducing a complex phospholipase D/phosphatidic acid signaling pathway that has not been reported for any galectin before. Gal-8 increases phosphatidic signaling, which enhances the activity of both ERK1/2 and type 4 phosphodiesterases (PDE4), with a subsequent decrease in basal protein kinase A activity. Strikingly, rolipram inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 86 publications
5
73
0
Order By: Relevance
“…We have previously shown that anti-Gal-8 autoantibodies produced by SLE patients block the interaction of Gal-8 with β1 integrins involved in its apoptotic action upon activated T cells (Norambuena et al, 2009). Autoantibodies against diff erent members of the galectin family such as Gal-1, -2, -3, and -4 been detected in patients with diff erent types of autoimmune diseases and in cancer (Lutomski et al, 1997;Giordanengo et al, 2001;Jensen-Jarolim et al, 2001;Lim et al, 2002;Romero et al, 2006;Montiel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that anti-Gal-8 autoantibodies produced by SLE patients block the interaction of Gal-8 with β1 integrins involved in its apoptotic action upon activated T cells (Norambuena et al, 2009). Autoantibodies against diff erent members of the galectin family such as Gal-1, -2, -3, and -4 been detected in patients with diff erent types of autoimmune diseases and in cancer (Lutomski et al, 1997;Giordanengo et al, 2001;Jensen-Jarolim et al, 2001;Lim et al, 2002;Romero et al, 2006;Montiel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…All these data indicate that incremented LFA-1 function promotes autoimmune disorders, whereas the contrary occurs when LFA-1 function decreases. Therefore, in addition to inducing apoptosis of activated T cells (Norambuena et al, 2009), Gal-8 might also exert an immunosuppressive action by blocking LFA-1 function. It has been reported that Gal-8 is endocytosed after binding to the cell surface (Carlsson et al, 2007), thus Gal-8 may remove LFA-1 from the cell surface and inhibit its interaction with ICAM-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations